Modern geotechnical design codes of practice : implementation, application and development - Hennessee, Patrick A. (Patrick Arnold); Fenton, Gordon A.; Hicks, Michael A.; Schweckendiek, Timo; Simpson, Brian (IOS, 2013)
The ground is one of the most highly variable of engineering materials. It is therefore not surprising that geotechnical designs depend on local site conditions and local engineering experience. Engineering practices, relating to investigation and design methods (site understanding) and to safety levels acceptable to society, will therefore vary between different regions. The challenge in geotechnical engineering is to make use of worldwide geotechnical experience, established over many years, to aid in the development and harmonization of geotechnical design codes. Given the significant uncertainties involved, empiricism and engineering judgment will undoubtedly always be an essential element of geotechnical design. However, rigorous and scientific approaches based on probability theory are finding increased attention in the calibration of modern geotechnical codes of practice and these codes can and should be used to aid fundamental engineering judgment. Containing contributions on Code Implementation, Code Application and Code Development, this book provides a single resource that code developers, practitioners, and researchers can use to understand the different choices made by national code developers around the world. Furthermore, the book highlights some of the key challenges faced worldwide concerning the ongoing process of harmonizing geotechnical design code specifications.